The teacher, a craftsman of his future. Fantasies of an utopia? - González González, Miguel Alberto (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2014)
The present paper is the result of a research developed in the University of the University of Manizales-Colombia “Vision of philosophers and writers on occurring of the contemporary university, re-built during 2008 and 2010”. Where a variety of difficult aspects gave the possibility to write this, among some of them the lack of academic strength, low of innovation, lack of relationship between practice and theory, lack of confidence in the own knowledge, and certain lack of interest of the teacher for his work, but also certain hope, true to occur without agony as a luck of victory for conquering on the part of the teacher they made way to this academic reflection; A teacher who craft his future and that he can still believe in the fantasies of an utopia. In the era of unbelief in the same for latin americans, where the strange seduces us, it is not uncommon for the teacher wanting to be a scientist, philosopher or expert on a particular topic, to abandon its mission first, be a mediator between the cultural productions, as technologies or theories and the popular cultures with its desire to conservation and the fears of the renewal. Thus, the evolution of teacher in education would be given by a set of political, economic, technological and social circumstances that are not always understood and that limit, in some way, the Act of teaching-learning, say that to not giving him a reading adapted to such difficulties could be in crisis the moral world reserves as he is understood to education. In this circumstance, to convey different times to those related to the first decade of the twentyfirst century that crosses the teacher; it requires a commitment with the thought, not with a particular ideology in order to weaken the walls that prevent the teacher get out of the rounding up, these walls are not only the physical order. As well as, the evolution of the teacher in the education is not given, it is a construction, it is an exercise of autonomy that, as the life is conquest day to day.